Omicron Severe Acute Respiratory Syndrome Coronavirus 2 Neutralization by Immunoglobulin Preparations Manufactured From Plasma Collected in the United States and Europe . (2nd September 2022) - Farcet, Maria R; Karbiener, Michael; Knotzer, Simone; Schwaiger, Julia; Kreil, Thomas R
Abstract: After >2 years of the coronavirus disease 2019 (COVID-19) pandemic, immunoglobulins (IGs) contain highly potent severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) neutralizing antibodies, based on the large proportion of United States (US) plasma donors who have gone through COVID-19 or vaccination against the virus. Neutralization of Omicron SARS-CoV-2 by antibodies generated after non-Omicron infection or vaccination has been lower though, raising concerns about the potency of IG against this new virus variant. Also, as plasma collected in the US remains the main source of IG, the neutralization of SARS-CoV-2 for plasma collected elsewhere has been less well studied. Here, we confirm Omicron neutralization by US as well as European Union plasma–derived IG lots. Abstract : Immunoglobulin preparations produced from plasma of COVID-19 recovered or vaccinated donors contain SARS-CoV-2 neutralizing antibodies. Neutralization of the Wuhan as well as the Omicron virus variant is shown for immunoglobulin manufactured from plasma collected in the US and EU.